Features of forming of motive skills for the schoolchildren of junior classes - Худолій, О. М.; Черненко, С. О. (Physical Education Theory and Methodology, 2013)
Target of work — to define the features of forming of motive skills for the schoolchildren of junior classes. Methods and organization of research. An analysis and generalization of data of scientific and special literature, scientific methods of theoretical level are in-process used, such, as an analogy, analysis, synthesis, abstracting, induction, and also scientific methods of empiric level : supervision, testing, experiment. In research took part, in every parallel of classes for 48 students, all are 172 students. Conclusions. Experiment of type 23 gave an opportunity to investigate the multivariable structure of the modes of process of studies to physical exercises of schoolchildren of 1—4 classes, to specify optimal correlations of amount of approaches, amount of reiterations in approach and interval of rest in the period of studies of «throws of ball», acrobatic exercises and gymnastic supporting jumps on the lessons of physical culture. On efficiency of process of educating of schoolchildren of 1—4 classes in vertical aim» positively the increase of amount of approaches influences the «throw of ball to 12, amounts of reiterations in approach to 3 times, the interval of rest lasts 60—180 p. For the schoolchildren of A-one an accent in the choice of the mode of educating is done on the amount of reiterations in approach; schoolchildren of the second class — on reduction to the interval of rest to 60 with; schoolchildren of the third class — on cooperation of amount of approaches and amount of reiterations in approach; schoolchildren of fourth class — on the amount of reiterations in approach and interval of rest. On efficiency of process of educating of schoolchildren of A-one of «cuverka forward» positively the increase of amount of approaches influences to 12 times, the amount of reiterations in approach hesitates within the limits of 1—3 times, interval of rest — 60—180 p. In the process of educating attention is accented on the amount of approaches. On efficiency of process of educating of schoolchildren of the second class of «cuverka forward» positively the increase of amount of reiterations influences in approach to 3 times, the amount of approaches hesitates within the limits of 6—12 times, interval of rest — 60—180 p. attention on the amount of reiterations of exercise is Accented in approach. On efficiency of process of educating of schoolchildren of the third class to the supporting jump of «leg in розь through a horse breadthways» positively the increase of amount of reiterations influences in approach to 3 times, the amount of approaches hesitates within the limits of 6—12 times, interval of rest — 60—180 p. attention on the amount of reiterations of exercise is Accented in approach. On efficiency of process of educating of schoolchildren of fourth class to the supporting jump, «bending feet through a goat breadthways» positively the increase of amount of reiterations influences in approach to 3 times, the amount of approaches hesitates within the limits of 6—12 times, interval of rest — 60—180 p. attention on the amount of reiterations of exercise is Accented in approach and amount of approaches.